Performance improvement of improved practical control method for two-mass PTP positioning systems in the presence of actuator saturation - Yakub, Mohd Fitri Mohd; Akmeliawati, Rini (2011)
The positioning systems generally need a good controller to achieve a fast response, high accuracy and robustness. In addition, ease and simplicity of controller design structure are very important for practical applications. For satisfying these requirements, NCTF controller has been proposed as a practical control method for two-mass rotary PTP positioning systems. However, the effect of the actuator saturation cannot be completely compensated due to integrator windup when the object parameter varies. This paper presents a method to further improve NCTF controller to overcome the problem of integrator windup. The improved NCTF controller is evaluated experimentally using rotary two-mass positioning system. The effect of the design parameters on the robustness of the improved NCTF with anti-windup integrator controller is evaluated and compared with NCTF without anti-windup integrator and the equivalent PID controller. The results show that the improved NCTF controller is effective to compensate the effect of integrator windup.